2019
DOI: 10.1136/ijgc-2018-000064
|View full text |Cite
|
Sign up to set email alerts
|

Localized high grade endometrial stromal sarcoma and localized undifferentiated uterine sarcoma: a retrospective series of the French Sarcoma Group

Abstract: ObjectiveHigh grade endometrial stromal sarcoma and undifferentiated uterine sarcomas are associated with a very poor prognosis. Although large surgical resection is the standard of care, the optimal adjuvant strategy remains unclear.MethodsA retrospective analysis of patients with localized high grade endometrial stromal sarcoma and undifferentiated uterine sarcomas (stages I–III) treated in 10 French Sarcoma Group centers was conducted.Results39 patients with localized high grade endometrial stromal sarcoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
0
21
0
3
Order By: Relevance
“…Recently, a retrospective, single-centre study evaluated prognostic factors in 40 patients affected by HG-ESS[56]; the combination of surgery with RT and ChT appeared to improve PFS in early-stage disease. These findings were confirmed by a retrospective analysis of the French Sarcoma Group in which multivariate analysis of adjuvant chemotherapy in completely resected HG-ESS and UUS was correlated with improved DFS[57]. Presently, with respect to the prospective studies which might validate adjuvant ChT in HG-ESS and UUS, current guidelines consider the use of postoperative ChT appropriate taking into account the high risk of recurrence characterising these diseases[6].…”
Section: Other Histotypesmentioning
confidence: 89%
“…Recently, a retrospective, single-centre study evaluated prognostic factors in 40 patients affected by HG-ESS[56]; the combination of surgery with RT and ChT appeared to improve PFS in early-stage disease. These findings were confirmed by a retrospective analysis of the French Sarcoma Group in which multivariate analysis of adjuvant chemotherapy in completely resected HG-ESS and UUS was correlated with improved DFS[57]. Presently, with respect to the prospective studies which might validate adjuvant ChT in HG-ESS and UUS, current guidelines consider the use of postoperative ChT appropriate taking into account the high risk of recurrence characterising these diseases[6].…”
Section: Other Histotypesmentioning
confidence: 89%
“…The role of lymphadenectomy in the surgical management of ESS patients is not conclusive. Lymph node involvement among these patients was uncommon, and no differences were found either in recurrence-free survival or in overall survival after performing lymphadenectomy (19)(20)(21). In our cohort, all the patients underwent surgery without lymphadenectomy under the direction of gynecologic, vascular and cardiac surgeons.…”
Section: Discussionmentioning
confidence: 83%
“…One of the retrospective studies reported that adjuvant radiotherapy and chemotherapy appear to improve overall survival. [ 17 ]…”
Section: Discussionmentioning
confidence: 99%